Clinician Acceptance and Adoption of PACS in Radiology Services: An Exploratory Study - Alhur, Anas (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2024)
This exploratory study explores the acceptance and adoption of Picture Archiving and Communication Systems (PACS) among clinicians practicing radiology services in Hail City, Kingdom of Saudi Arabia. A survey was conducted with 142 clinicians from various specialties from four public hospitals located there and focused on clinician satisfaction with inpatient and outpatient services as well as perceptions about PACS usage as well as the overall impression of radiology services; data analysis included descriptive statistics. Findings show high levels of patient satisfaction with waiting times for investigations in both inpatient and outpatient settings; Radiology staff were perceived as approachable and willing to discuss clinical information with participants, PACS usage was highly rated by clinicians for viewing reports and images, participants reported high satisfaction with image quality, reliability and ease of use; and PACS was seen to shorten reporting speeds as well as waiting times. Correlations were observed between clinician age, approachability of radiology staff, speed of reporting, wait time for investigations and overall satisfaction with PACS use in radiology practice, adoption rates and satisfaction levels of users; continuous improvements to efficiency and service awareness, as well as improvements to adoption rates, are key components to increasing adoption rates and satisfaction levels among healthcare institutions and radiology practitioners alike. Future research could include patient perspectives to gain a holistic view of its impact on overall healthcare experiences.